Pharmacological and toxicological studies of a novel goserelin acetate extended-release microspheres in rats - Yutong, Mao; Liang, Ye; Chunjie, Sha; Xiaolin, Guan; Xiaoyan, Gong; Lin, Dong; Guangying, Du; Xuemei, Zhang; Xiaobo, Cen; Jingwei, Tian; Pengfei, Yu; Hongbo, Wang (Frontiers in Pharmacology, 2023)
LY01005 is an investigational new drug product of goserelin acetate which is formulated as extended-release microspheres for intramuscular injection. To support the proposed clinical trials and marketing application of LY01005, pharmacodynamics, pharmacokinetics and toxicity studies were performed in rats. In the pharmacological study in rats, LY01005 induced an initial supra-physiological level increase of testosterone at 24 hours post-dosing which then rapidly fell to castration level. The potency of LY01005 was comparable to the comparator Zoladex® but its effect lasted longer and more stable. A single-dose pharmacokinetics study in rats demonstrated that the Cmax and AUClast of LY01005 increased in a dose-proportional manner in the range of 0.45-1.80 mg/kg and the relative bioavailability was 101.0% between LY01005 and Zoladex®. In the toxicity study, almost all of the positive findings of LY01005 in rats including the changes in hormones (FSH, LH, testosterone, progestin) and in reproductive system (uterus, ovary, vagina, cervix uteri, mammary gland, testis, epididymis and prostate) were related to the direct pharmacological effects of goserelin. Mild histopathological changes in foreign body removal reaction induced by excipient were also observed. In conclusion, LY01005 displayed a sustained-release profile of goserelin, and exerted a continuous efficacy in vivo in animal models, which had a comparable potency but with a more sustained effect than that of Zoladex®. The safety profile of LY01005 was largely the same with Zoladex®. These results strongly support the planned LY01005 clinical trials.